A Unified Call-to-Prayer Framework in Muslim World - Naeem Al-Oudat; Abdel Ilah Alshbatat (Institute of Advanced Engineering and Science, 2014)
In many Muslim countries there are many sounds that are fired at nearly the same time via loudspeakers. This sound is a call-to-prayer (Azan). Azan is fired from the so-called mosques in many countries where, theses mosques are still using its own timing to trigger such call and its own amplifier gain regardless of other mosques in the region. This results in an out of sync call-to-prayer firing and a very noisy and distracting mix of sounds in many places at the same region. In this paper, a unified call-to-prayer framework is proposed that sheds light on these issues and gives solution directions for the above mentioned issues in the currently used systems.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5758